(Lipoxygenese in soybean Products) - Rosidi, Bakri Rosidi (Warta Industri Hasil Pertanian, 1987)
Lipoxygenase in an enzyme which limit the use of soybean as a protein source food. Research on this matter has been widely done. This paper discussed the property of lipoxygenase, off-flavor products resulted, its effect on soybean protein and its inactivation.